Account of a Circular Building, and other Ancient Remains, discovered in South Uist (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author gives the account of C. Gordon, who unearthed an unknown structure on South Uist. He describes the structure's dimensions and lists the items found inside. He then goes on to compare this find to the brochs found on Orkney and Shetland.